Radical nephrectomy with resection of vena cava thrombus using extracorporeal circulation and deep hypothermic circulatory arrest - Nason, Gregory J.; Ajib, Khaled; Tan, Guan Hee; Woon, Dixon T.S.; Christakis, George T.; Nam, Robert K. (Canadian Urological Association Journal, 2020)
Introduction: Patients with renal cell carcinoma (RCC) with level 3 or 4 caval thrombus have a poor prognosis, with reported five-year survival rates of 30–40%. The aim of this study was to assess the perioperative morbidity and long-term oncological outcomes for radical nephrectomy with resection of vena cava thrombus using a combined surgical approach, including extracorporeal circulation and deep hypothermic circulatory arrest. Methods: A retrospective review was performed of the institutional case log to identify all radical nephrectomies with caval thrombus performed from January 2006 to May 2020. Results: Twenty-five patients were identified with level 2 thrombus in one (4%), level 3 thrombus in eight (32%), and level 4 in 16 (64%). The median followup was 20.6 months (range 0.2–133.3). The median age at surgery was 68.4 years (range 44.2–85.5). Twenty-one (84%) patients were symptomatic at presentation. Six (24%) patients had distant metastases at diagnosis. The median circulatory arrest time was 15 minutes (range 6–35). The 30-day grade ≥3 complication rate was 8%. The 30-day mortality rate was 8%. The one-year, two-year, three-year, and five-year recurrence-free survival (RFS) rates were 53%, 18%, 10%, and 10%, respectively. The median time to systemic treatment was 7.7 months (range 1.2–25.7). The one-year, two-year, three-year, and five-year overall survival (OS) rates were 70%, 43%, 36%, and 31%, respectively. Conclusions: Radical nephrectomy with resection of vena cava thrombus using extracorporeal circulation and deep hypothermic circulatory arrest is associated with some morbidity and mortality but remains a safe and effective strategy for advanced RCC patients who would otherwise be managed palliatively.